Households’ Income in Romania for the 1918–2018 Century: Resources and Social Protection - Ilie, Simona (Calitatea Vieții, 2018)
The paper addresses the changes that have occurred in household incomes in Romania after its constitution as a national state (1918). Land work, industrialization, migration, vocational training and social policy, as income determinants, are discussed in the context of the three great periods that have shaped the last century in Romania: pre-communist, communist and post-communist.